Development of an Innovative Nanotransdermal Formulation Utilizing an Optimal Combination of Acyclovir and Omeprazole to Improve Antiviral Efficacy - E. Sri Divya; Nansri Saha (International Journal of Biomedical Innovations and Engineering, 2024)
The study effectively created nanogel formulations of Acyclovir and Omeprazole using the solvent diffusion technique. Among the various formulations (F1–F9), F9 was identified as the most suitable for gel preparation based on its pH evaluation. Drug content analysis, performed using UV-spectroscopy, confirmed the homogeneity of the prepared nanogels, which appeared opaque, free of lumps, particles, or aggregates. The spreadability assessment of F9 demonstrated excellent spreadability, while viscosity values for all formulations ranged between 3268 and 3528 cps, indicating stability. The in-vitro dissolution tests showed that formulation F9 demonstrated a significantly improved rate of dissolution. Further characterization of F9 showed a particle size of 687.4 nm, a PDI of 0.842, and a zeta potential of -43.7 mV. TEM imaging confirmed the spherical shape and smooth surface of the particles, with sizes around 650 nm. A comparative in-vitro release study between the F9 nanogel and the marketed acyclovir formulation (MF) demonstrated that the nanogel provided sustained drug release and superior antiviral activity. This indicates that transforming Acyclovir and Omeprazole into a nanogel formulation significantly enhances their therapeutic efficacy compared to conventional formulations.
Keywords: Acyclovir; Anti-Viral Activity; Formulation; Nano Transdermal; Omeprazole